Modeling development of breast cancer: from tumor microenvironment to preclinical applications - Tang, Ruizhi; Liu, Xi-Qiu (Frontiers in Pharmacology, 2024)
Please find herewith the revised version of our manuscript of a review entitled "Modeling Development of Breast Cancer: from Tumor Microenvironment to Preclinical Applications" by Ruizhi Tang and Xi-Qiu Liu.We thank the reviewers for their useful remarks, which help us to improve the manuscript.We have added Figure 2 into the manuscript to compare and contrast these four models, as well as provided the examples of application for pharmacology audience. The relevant description was also updated in the first paragraph of Section 4 Culture models for breast cancer therapy studies. We have also emphasized two typical discoveries made by more complex models instead of the traditional epithelium-focussed models in Section 4.3. Tumor organoids and Section 4.4. Organs-on-a-chip as following. All the corresponding revisions in the manuscript are clearly highlighted in blue.Please find below a point-by-point answer to the reviewer's comments. We believe that our manuscript has been significantly improved and it is ready for publication.Sincerely Yours,